2018
DOI: 10.1192/bjp.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Whooley questions and the Edinburgh Postnatal Depression Scale in identifying depression and other mental disorders in early pregnancy

Abstract: BackgroundThere is limited evidence on the prevalence and identification of antenatal mental disorders.AimsTo investigate the prevalence of mental disorders in early pregnancy and the diagnostic accuracy of depression-screening (Whooley) questions compared with the Edinburgh Postnatal Depression Scale (EPDS), against the Structured Clinical Interview DSM-IV-TR.MethodCross-sectional survey of women responding to Whooley questions asked at their first antenatal appointment. Women responding positively and a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 150 publications
(187 citation statements)
references
References 26 publications
3
176
1
7
Order By: Relevance
“…We found that the prevalence of high levels of depressive symptoms around the time of GDM diagnosis was 28% (pooled OR 2.08) and following diagnosis was 26% (pooled OR 1.41). This is higher than that expected in the general pregnant population [26,27]. In the postpartum, the prevalence of depression in women diagnosed with GDM during pregnancy was 13% (pooled OR 1.59).…”
Section: Main Findingsmentioning
confidence: 65%
See 1 more Smart Citation
“…We found that the prevalence of high levels of depressive symptoms around the time of GDM diagnosis was 28% (pooled OR 2.08) and following diagnosis was 26% (pooled OR 1.41). This is higher than that expected in the general pregnant population [26,27]. In the postpartum, the prevalence of depression in women diagnosed with GDM during pregnancy was 13% (pooled OR 1.59).…”
Section: Main Findingsmentioning
confidence: 65%
“…Of the 17 studies not included in meta-analysis (Tables S2 and S3), there were 11 for which the time of depression measurement in the antepartum in relation to GDM diagnosis could not be ascertained (references 18,20,23,27,30,35,40,46,49,51 and 60 in Appendix S2). One study provided only results stratified by BMI (reference 59 in Appendix S2) and another used depression as exposure not outcome (reference 53 in Appendix S2).…”
Section: Odds and Prevalence Of High Levels Of Antenatal Depressive Smentioning
confidence: 99%
“…The purpose of the WENDY study was to determine the prevalence of antenatal common mental disorders and to investigate the effectiveness and cost-effectiveness of the Whooley questions and the Edinburgh Postnatal Depression Scale (EPDS) in identifying antenatal depression. 6 …”
Section: Methodsmentioning
confidence: 99%
“…Perinatal mental health encompasses the mental and emotional health of women during pregnancy and in the year after birth (Noonan, Doody, Jomeen, & Galvin, ). The term perinatal mental health problems (PMHPs) refers to the range of psychological distress that healthcare professionals may encounter during this period which may range from depression and anxiety to serious mental health problems (Howard et al, ; Noonan, Doody, et al, ). PMHPs are among the most common morbidities experienced by women with international rates of 13–25% reported (Kingston et al, ).…”
Section: Introductionmentioning
confidence: 99%